TRENDS IN THE TRAINING OF IT SPECIALISTS: EXPERIENCE OF INTERUNIVERSITY COOPERATION - Mietule, Iveta; Holubeva, Aksana; Ziankova, Inha; Lisichonak, Alena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The active development of information technology determines the need to ensure the supply-demand balance of labour in the labour market. In modern conditions, it is necessary not only to increase the output of specialists with IT knowledge and skills, but also to orient all students, regardless of specialty, to receive other flexible digital skills. The main aim of the research study is to justify the need for the priority development of IT specialties and flexible digital skills in higher educational institutions, to identify its main trends at Polotsk State University, in the framework of cooperation with Rezekne Academy of Technologies, in particular. The research methodology is based on the principles of system analysis, formal logic and an interdisciplinary scientific approach. The novelty of the research is to generalize the unique experience of training specialists at the Faculty of Information Technology of Polotsk State University, based on the practical orientation of the learning process. In addition, the paper provides information characterizing the development trends of the IT sector in Belarus. The following recommendations are proposed: 1) the implementation of the principle of building up cross-functional skills by students at the first stage of higher education, and then this is a deep specialization of the workforce throughout life; 2) the use of creative educational technologies; 3) the creation of a web tool that implements the task of creating flexible digital skills among the population of older working age and children through training in the Republic of Latvia and the Republic of Belarus; 4) the implementation of joint educational programmes with a double diploma.